An Immunohistochemical Study Of Survivin Expression In Normal And In Transformed Cells [QH585.2. I82 2006 f rb]. - Alias, Iskandar Zulkarnain (2006)

(untitled)
Survivin is a new member of the inhibitors of apoptosis protein (IAP) family,selectively over-expressed in common human cancers but not in normal adult tissues. It is also expressed in cancer cell lines.